Respuesta :
Answer:
First, let's address the general case.
When we have two points (a,b) and (c,d)
The distance between those points can be written as:
D = √( (a - c)^2 + (b - d)^2)
In this case, the points are:
(-2,4) and (2,4)
Then the distance is:
D = √( (-2 - 2)^2 + (4 - 4)^2) = √(-4)^2 = 4.
The equivalent expression to this is: |-2| + |2|
because:
I-2I = 2
I2I = 2
I-2I + I2I = 2 + 2 = 4.
Answer:
D = √( (a - c)^2 + (b - d)^2)
In this case, the points are:
(-2,4) and (2,4)
Then the distance is:
D = √( (-2 - 2)^2 + (4 - 4)^2) = √(-4)^2 = 4.
The equivalent expression to this is: |-2| + |2|
because:
I-2I = 2
I2I = 2
I-2I + I2I = 2 + 2 = 4.
Step-by-step explanation: